2007
DOI: 10.1063/1.2775297
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent phase transition of EuO on MgO(100)

Abstract: Articles you may be interested inOxygen-vacancy-induced room-temperature magnetization in lamellar V2O5 thin films J. Appl. Phys. 116, 163904 (2014) We investigated the changes of magnetic properties and phase transition in EuO films grown on a MgO͑100͒ substrate as a function of temperature. As the temperature was varied, we observed a clear phase transition and polarization change at 69 K using spin resolved photoemission spectroscopy and low energy electron diffraction. We will elucidate the temperature dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
(11 reference statements)
2
3
0
Order By: Relevance
“…Figure 2(b) shows the Eu M 5 -edge XAS spectrum measured from a ESMO film on LSAT. It is clearly shown that the Eu M 5 -edge spectrum of the ESMO thin film is in good agreement with that of Eu 3þ , as previously reported for Eu 2 O 3 (a dashed curve) [44]. Figure 2(c) shows the Mn L 2;3 -edge XAS spectra probing the unoccupied Mn 3d states via the 2p-3d dipole transition for the four different strained ESMO thin films.…”
Section: Resultssupporting
confidence: 85%
“…Figure 2(b) shows the Eu M 5 -edge XAS spectrum measured from a ESMO film on LSAT. It is clearly shown that the Eu M 5 -edge spectrum of the ESMO thin film is in good agreement with that of Eu 3þ , as previously reported for Eu 2 O 3 (a dashed curve) [44]. Figure 2(c) shows the Mn L 2;3 -edge XAS spectra probing the unoccupied Mn 3d states via the 2p-3d dipole transition for the four different strained ESMO thin films.…”
Section: Resultssupporting
confidence: 85%
“…The splitting energy of the O 2p state is consistent with the band calculation in Figs. 2(g4) and 2(x4), and also with the spin-resolved photoemission spectroscopy results [17]. Here, the O 2p bands at the higher and lower binding energies are attributed to the majority-and minority-spin states, respectively.…”
supporting
confidence: 73%
“…To date, changes in the electronic structure of EuO at T C have been investigated using infrared [8][9][10][11], x-ray adsorption [12], and angle-integrated photoemission spectroscopy [13][14][15][16][17]. Although the obtained data show the change in the electronic structure caused by magnetic ordering, the change in the band structure to clarify the momentum dependence of the 4f state and its relation to the exchange interaction have never been investigated.…”
mentioning
confidence: 99%
“…Figure 1B shows the PES spectra of 2 nm EuO/ 5 nm SrO/SrTiO 3 [Figure 1B(1)], 5 nm EuO/SrTiO 3 [Figure 1B(2)], and 5 nm SrO/SrTiO 3 films [Figure 1B(3)] measured at 10 K for h] = 38 eV. The 2-nm EuO/5-nm SrO/ SrTiO 3 film only presented Eu 2+ 4f and O 2p [Figure 1(b1)] although the 5-nm EuO/SrTiO 3 displayed Eu 3+ 4f and metallic states originating from Eu 2 O 3 and Eu metal [Figure 1B(2)], respectively (Lee et al, 2007). These results suggest that the SrO buffer layer prevents oxygen diffusion from the SrTiO 3 substrate to the EuO ultrathin film.…”
Section: Resultsmentioning
confidence: 99%